I know what I saw [videorecording (DVD)] - Fox, James, 1968- (UFO TV, 2015)
"The most credible UFO witnesses from around the world tell stories that challenge reality in 'I Know What I Saw,' a documentary guaranteed to change the way we see the universe. Director James Fox brings together the testimony of Air Force Generals, Astronauts, Military & Commercial Pilots, Government and FAA Officials from seven countries; their accounts reveal the reasons those involved at the highest levels have chosen Government Secrecy over Public Disclosure."--Container.